Implementation of Islamic Religious Education Learning For Children With Special Needs - Eva Sofia Sari; Fitrah Sugiarto (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The lack of community guidance and awareness in dealing with education for Children with special needs (ABK) greatly affects the education system, including the lack of Islamic Religious Education teachers with special educational backgrounds, while Islamic Education learning at schools is urgently needed to be developed continuously. The objectives of this study were to find the concept of PAI learning for ABK at Mataram State Special School, to analyze the implementation of PAI learning for ABK at Mataram State Special School, and to find opportunities and challenges for PAI learning at Mataram State Special School . This research was descriptive qualitative research which used type of case study, data collection methods used by the researcher were interviews, observation and documentation. Data analysis used were data collection, data presentation, data reduction and conclusion. Checking the validity of the data used the degree of trust (credibility), the degree of transferability (transferability), the degree of dependability (dependability), and the degree of certainty (confirmability). The results of this study are that the concept of PAI learning for ABK has not been packaged specifically, where no deep specificity has been found in the materials, media and learning methods for ABK. Planning and implementation of learning have not effectively run with an incompatibility between planning and implementation. Islamic education learning opportunities are Islam as a way of life so that students become confident, patient and grateful human beings; they can protect themselves from global developments, and are able to understand and practice moderate Islam. meanwhile,